Economic, social and behavioural aspects of covid-19 in the first wave of the pandemic in Slovenia - Perković, Ksenija (Monitor ISH, 2024)
In the spring of 2020, an international study survey entitled ‘Social, ethical and behavioural aspects of COVID-19’ (SEBCOV) was conducted in Slovenia, Italy, United Kingdom, Malaysia and Thailand. These countries implemented strict public health preventive measures to contain the pandemic during its first wave. The research focused on the question of which factors should guide decisions on the manner and extent of the introduction of measures such as general quarantine, isolation, social distancing and travel restrictions. This paper analyses the results of an anonymous online survey carried out in Slovenia between 1st June and 31st July 2020 and presents a set of results relating to the understanding and attitudes of Slovenian respondents in relation to the first wave epidemic and the measures taken at that time. As there was insufficient data on the social, ethical and behavioural aspects of these measures during the first wave, we analysed these aspects in order to help to adopt appropriate non-pharmaceutical interventions (NPIs) in mitigating COVID-19 and other pandemics in the future.
Keywords: Covid-19; first wave; non-pharmaceutical interventions (NPIs); pandemic; pandemije; Slovenija; survey; Varnostni ukrepi; vladni ukrepi